Investigating the impacts of airborne dust on herbicide performance on Amaranthus retroflexus - Firouzeh Sharifi Kalyani; Sirwan Babaei; Yasin Zafarsohrabpour; Iraj Nosratti; Karla Gage; Amir Sadeghpour (Scientific Reports, 2024)
Abstract Dust pollution poses environmental hazards, affecting agriculture through reduced sunlight exposure, photosynthesis, crop yields, and food security. This study explores the interference of dust pollution on herbicide efficacy to control weeds in a semi-arid region. In a factorial experiment conducted in 2019 and replicated in 2020, the interaction of dust and various herbicide applications, including bentazon, sulfosulfuron, tribenuron-methyl, aminopyralid + florasulam, foramsulfuron + iodosulfuron + thiencarbazone, 2,4-D + MCPA, and acetochlor, in controlling Amaranthus retroflexus L. were assessed. Dust induced a 9.2% reduction in the total chlorophyll content of A. retroflexus, while herbicide application independently led to a 67.5% decrease. Contrary to expectations, herbicides performed better in dust, except bentazon, which caused a 28% drop in plant height and a 29% decrease in total biomass compared to non-dust conditions. Both herbicides and dust exerted suppressive effects on A. retroflexus's leaf and stem weights and overall biomass. Despite dust presence, tribenuron-methyl (95.8%), aminopyralid + florasulam (95.7%), sulfosulfuron (96.5%), and foramsulfuron + iodosulfuron + thiencarbazone (97.8%) effectively controlled A. retroflexus. These findings indicate that dust's effect on herbicide efficacy is herbicide-dependent but except bentazon, dust generally increased herbicide efficacy and amplified the control of A. retroflexus.